RELIGION, STATE, AND IDEOLOGY IN INDONESIA: A HISTORICAL ACCOUNT OF THE ACCEPTANCE OF PANCASILA AS THE BASIS OF INDONESIAN STATE - Ismail, Faisal (Universitas Islam Indonesia, 2018)
On June 1, 1945, in the session of the Invistigating Body for the Preparation for Indonesian Independence, Soekarno, representing the Religiously Neutral Nationalists, proposed Pancasila as the basis of the Indonesian State. On the other hand, the Muslim Nationalists advocated Islam for the purpose. After long debates, the two factions achieved a political compromise and agreed the use of Pancasila as the basis of the state. Following the 1955 general election, a new constitution was drafted and the issue of the basis of the state was debated again. The Muslim Nationalists and the Religiously Neutral Nationalists did not achieve a political compromise. Due to this political deadlock, President Soekarno on July 5, 1959 issued a decree proclaiming a return to the 1945 Constitution. Since that time, Pancasila has been permanently used as the basis of the state up to the present. Not only do the Muslims accept Pancasila, but also defend it.